2023
DOI: 10.1002/jso.27207
|View full text |Cite
|
Sign up to set email alerts
|

Tumor deposits are associated with a higher risk of peritoneal disease in non‐metastatic colorectal cancer patients

Abstract: Background and Objectives Tumor deposit (TD) is a poor prognostic factor in colorectal cancer (CRC) patients. This study aimed to determine whether TD carry the same risk of peritoneal recurrence as known high‐risk (HR) features in CRC patients. Methods A retrospective cohort‐study of stage I−III CRC patients from 2010 to 2015 was conducted. TD group was defined by the presence of TD on histopathology whereas HR group was defined by the presence of obstruction, perforation, or T4‐stage. Results A total of 151 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The study suggests that non‐metastatic CRC patients with tumor deposits (TDs) identified on pathology have an increased risk of peritoneal carcinomatosis, which typically occurs at 1 year from surgical resection. It also provides evidence that TD patients have outcomes worse than HRFs CRC patients 1 . Although the study unveils a novel observation, an aspect of concern arose during the analysis.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The study suggests that non‐metastatic CRC patients with tumor deposits (TDs) identified on pathology have an increased risk of peritoneal carcinomatosis, which typically occurs at 1 year from surgical resection. It also provides evidence that TD patients have outcomes worse than HRFs CRC patients 1 . Although the study unveils a novel observation, an aspect of concern arose during the analysis.…”
mentioning
confidence: 87%
“…It also provides evidence that TD patients have outcomes worse than HRFs CRC patients. 1 Although the study unveils a novel observation, an aspect of concern arose during the analysis. The analytical methodology employed was not suitably tailored to fulfill these objectives.…”
mentioning
confidence: 99%
See 1 more Smart Citation